2017
DOI: 10.3389/fimmu.2017.00948
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan from Immunobiotic Lactobacillus rhamnosus Improves Resistance of Infant Mice to Respiratory Syncytial Viral Infection and Secondary Pneumococcal Pneumonia

Abstract: Several research works have demonstrated that beneficial microbes with the capacity to modulate the mucosal immune system (immunobiotics) are an interesting alternative to improve the outcome of bacterial and viral respiratory infections. Among the immunobiotic strains with the capacity to beneficially modulate respiratory immunity, Lactobacillus rhamnosus CRL1505 has outstanding properties. Although we have significantly advanced in demonstrating the capacity of L. rhamnosus CRL1505 to improve resistance agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(109 citation statements)
references
References 33 publications
8
101
0
Order By: Relevance
“…A similar protective effect against RSV‐pneumococcal superinfection, mediated by TLR‐3 activation, was observed in infant mice with the intranasal administration of viable, but also nonviable Lactobacillus rhamnosus or its purified peptidoglycan 101 . In addition, treatment of mice with anti‐IFN‐γ or anti‐IL‐10 monoclonal antibodies diminished their capacity to reduce lung bacterial cell counts and lung tissue injuries 102 . Factors expressed by commensal microbiota may provide additional protection against viral infections.…”
Section: Airway Microbiomementioning
confidence: 69%
See 1 more Smart Citation
“…A similar protective effect against RSV‐pneumococcal superinfection, mediated by TLR‐3 activation, was observed in infant mice with the intranasal administration of viable, but also nonviable Lactobacillus rhamnosus or its purified peptidoglycan 101 . In addition, treatment of mice with anti‐IFN‐γ or anti‐IL‐10 monoclonal antibodies diminished their capacity to reduce lung bacterial cell counts and lung tissue injuries 102 . Factors expressed by commensal microbiota may provide additional protection against viral infections.…”
Section: Airway Microbiomementioning
confidence: 69%
“…Conversely, changes in microbial community composition constitute a heightened element of risk towards viral respiratory infections and bacterial superinfections (Figure 4). 101,102 …”
Section: Airway Microbiomementioning
confidence: 99%
“…Some LAB microbe-associated molecular patterns (MAMPs) are able of working together with the Toll-like receptor-2 (TLR2), TLR6 and nod-like receptors [94]. Moreover Lactobacillus salivarius JTB07 and Lactobacillus reuteri JTB07 have been reported to upregulate the expression of IL-12, IL-8, IL-6, and IL-1, while Lactobacillus acidophilus JTB05 to upregulate the interferon-gamma expression level of their host cells [45,158,164]. Lactobacillus salivarius UCC 118 and Lactobacillus johnsonii LJ-1 were reported to enhance the IgA response and phagocytic activity in head-kidney leucocytes [165].…”
Section: Discussionmentioning
confidence: 99%
“…In relationship with the protection against RSV-pneumococcal superinfection, the study revealed that peptidoglycan from Lactobacillus rhamnosus CRL1505. Considerably enhanced lung CD3+CD4+IFN-γ+, and CD3+CD4+IL-10+ T cells plus CD11c+Sigle cF+IFN-β+alveolar macrophages with the resulting of increases of IFN-γ, IL-10, and IFN-β in the respiratory tract [75,76]. Nasal administration of Lactobacillus rhamnosus CRL1505 strain to malnourished mice under recovery reduced quantitative and qualitative alterations of CD4+T cells in the bone marrow, thymus, spleen and lung as well, CRL1505 treatment increased Th2-cytokines; interleukin 10 and 4 in respiratory and systemic compartments [77].…”
Section: Prevention and Management Of Respiratory Tract Disordersmentioning
confidence: 99%
“…For example, it has been shown that intranasal administration of Lactobacillus rhamnosus can aid in resisting RSV infection in infant mice (239). Another study suggested that this was due to a priming effect, showing that nonviable L. rhamnosus or the bacterial cell wall component peptidoglycan can enhance inflammatory responses in a TLR3-dependent manner (240). In a similar manner, TLR3-dependent priming with the upper respiratory tract-resident species Corynebacterium pseudodiphtheriticum also improved the outcome of RSV and secondary S. pneumoniae infection (241).…”
Section: Lung Microbiome In Host Tolerancementioning
confidence: 99%